Sistem Pakar dalam Akurasi Deteksi Pendarahan pada Kehamilan Menggunakan Metode Forward Chaining - Rivo Stephano; Y Yuhandri (Rektorat Universitas Putra Indonesia YPTK Padang, 2020)
The occurrence of bleeding in pregnancy is one of the most complications experienced by pregnant women. The limited knowledge possessed by pregnant women about the risks and dangers of bleeding during pregnancy and wrong or late handling when bleeding occurs is one of the factors that cause bad conditions that occur, namely fetuses and pregnant women can die due to bleeding experienced. This study aims to determine the level of accuracy in diagnosing bleeding that occurs in pregnancy by using the Forward Chaining method precisely and accurately. The data processed in this study were as many as 20 data which came from patient medical records and interviews with experts at RSKIA Sukma Bunda Payakumbuh. The processing stages consist of preparing input data, determining decision tables, creating rules, tracking processes, making decision trees, and tracking results. The results of testing this method are that there are 90% of patients who experience bleeding in pregnancy are based on the results of the consultation entered by the user. The results of this test have been able to diagnose bleeding in pregnancy quickly and accurately using the Forward Chaining method and can be recommended to help the doctor in the emergency room to diagnosing bleeding in pregnancy